Effect of Performance Management on Employee Productivity in The Fuel Refinery and Its Beneficial Impact on Work-Life Balance and Operational Excellence - S, Sudarshan; Xavier, Priya (International Journal of Accounting and Economics Studies, 2025)
This study explores concise explanations of performance management, its definition, its cycle, and recommended practices, the characteristics of a performance management system, and its prospects. This study underscores the indispensable function of performance management in optimising employee productivity and operational efficiency in the fuel refineries. Through a survey directly from the employees of fuel refineries in the north-eastern states of India, the data were collected. Individual interviews were conducted with each employee regarding their performance. The research was conducted using a mixed-method approach, and questionnaires were administered by the lower-management engineers. It was found that there was a considerable difference in employee productivity observed between employees with higher performance management and those with lower performance management through an Effect size of 1.39 for Cohen’s d (p < 0.001). This supports the basis of the study being conducted on employees with higher performance management to test further the hypothesis that employee productivity and operational excellence are positively influenced by Work-Life Balance. Employees with higher performance management had enhanced operational excellence and employee productivity. Managers can determine strategic growth prospects and evaluate the company's performance in comparison to industry peers using performance evaluation methods like benchmarking and balanced scorecards. Managers may inspire staff members to pursue excellence and contribute to the success of the company by setting performance goals, giving frequent feedback, and offering rewards for reaching them.
Keywords: Performance Management; Employee Productivity; Fuel Refinery; Work-Life Balance; Organizational Efficiency